Optimizing optimal path trace back system for Smith-Waterman algorithm using structural modelling technique: article - Saliman, Nur Farah Ain (2012)
back system for Smith-Waterman Algorithm using Structural Modelling Technique. The objectives for this paper are to optimize the best trace back scanning performance and also to design the simple architecture in order to reduce the runtime. It focuses on the complexity in the trace back scanning architecture design based on structural modelling technique. Due to the increasing number of the population, it also affected the increases number of probability in Deoxyribonucleic Acid (DNA) sequences alignment. This will cause disadvantages in the performance and speed level of the Smith-Waterman Algorithm. Thus, based on other researchers there was various kind of method being use in order to overcome this problem. Then, the structural modelling is being use in this project in order to trace back by scanning the Smith-Waterman matrix calculation and find the optimal path. The paper was to study on theoretical and a simulation technique to complete the result.